Depressive symptoms faced by non-native international medical students in China during COVID-19 - Xiang, Gao; Ahmad, Muhammad Ishfaq; Zhuang, Weiqing; Rehman, Ramiz Ur; Naseem, Muhammad Akram (Frontiers in Psychology, 2022)
This study examines depressive symptoms faced by non-native international medical students studying in China during the COVID-19 pandemic. The targeted population for this cross-sectional study included non-native medical students studying in Chinese universities. This study used convenience sampling. An online, self-administered questionnaire was distributed to international medical students studying in Chinese universities from February 2020 to June 2021. The questionnaire collected demographic data, information regarding struggles faced, and used the CES-D-10 Likert scale to assess both the challenges and depression symptoms, respectively. By analyzing the 1,207 students’ responses, the study found that students with poor Chinese language were two times more likely to suffer from depressive symptoms (OR = 2.67; value of p 0.00). Moreover, female students were found more prone (76.35%) than their male counterparts (44.96%). The study found that food adaptability, health issues, accommodation issues, and financial issues were related factors contributing to depressive symptoms among non-native international medical students during the COVID-19 pandemic. The study tried to highlight the factors that resulted in depressive symptoms among non-native international medical students, and the findings may help diplomatic representatives take necessary actions to help their citizens during this difficult time.